Harmony and hierarchy: A decolonial social psychological analysis of rural community life in Indonesia - Gautam Makwana (Dynamics of Rural Society Journal, 2027)
This comprehensive review article analyzes the social psychology of rural community life in Indonesia, examining how cultural ideals of harmony and social hierarchy shape interpersonal behavior, identity formation, and community norms. Despite growing scholarly interest, existing research remains fragmented across disciplines and has not been critically synthesized through a decolonial lens that treats indigenous psychological constructs on their own terms. To address this gap, a systematic literature review was conducted in accordance with the PRISMA 2020 guidelines across the Scopus, Web of Science, PubMed, Google Scholar, and Garuda databases. The inclusion criteria comprised peer-reviewed empirical studies published between 2014 and 2024 that focused on rural Indonesian communities. Thematic synthesis, guided by Braun and Clarke’s (2021) framework and incorporating a decolonial analytical lens, was applied to the 52 included studies. Three main findings emerged. First, gotong royong (mutual cooperation) functions both as a mechanism of social cohesion and as a tool of informal social control. Second, rasa malu (socially oriented shame) operates as a pre-emptive regulatory emotion that enforces conformity but suppresses mental health help-seeking. Third, tahu diri (knowing one’s place) maintains age and gender hierarchies while facing challenges from youth migration and digital media. Theoretically, this review advances understanding by reconceptualizing harmony and hierarchy as integrated, dynamic psychological strategies for navigating interdependent social ecologies. The findings cautiously suggest that community-based, culturally attuned approaches may enhance mental health and development policies, although these implications require further empirical testing through intervention research.